Classroom discourse of Malay language lesson: A critical analysis - Idris Aman,; Rosniah Mustaffa, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
Research on the teaching and learning process of the Malay language in the classroom usually focuses on the method, content, strategy and teaching aids. Moving away from this norm, this research article examines the process from the discourse analysis perspective called pedagogic discourse analysis, with an adaptation of Fairclough’s Critical Discourse Analysis Framework (1992; 1995). The discussion is based on several hours of teaching-learning case study conducted in a secondary school classroom, which emphasizes integrated curriculum in an attempt to understand the unseen social processes, i.e. teacher dominance in discourse. The research findings indicate that teacher dominance is concealed in turn-taking system, types of questions posed by the teacher, discourse control and the overall structure of the discourse, which have their implications on the implementation of the National Education Philosophy. Contrary to the emphasis on student centredness and thinking skills as laid out by the Integrated Curriculum for Secondary School, it is found that the nature of the learning process in the classroom hardly focused on students’ thinking skills. This article argues that students should be given the opportunity to exercise their critical and creative potentials